2019
DOI: 10.1016/j.steroids.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

COUP-TFII revisited: Its role in metabolic gene regulation

Abstract: Chicken Ovalbumin Upstream Promoter Transcription Factor II (COUP-TFII) is an orphan member of the nuclear receptor family of transcriptional regulators. Although hormonal activation of COUP-TFII has not yet been identified, rodent genetic models have uncovered vital and diverse roles for COUP-TFII in biological processes. These include control of cardiac function and angiogenesis, reproduction, neuronal development, cell fate and organogenesis. Recently, an emerging body of evidence has demonstrated COUP-TFII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 74 publications
0
23
0
1
Order By: Relevance
“…Next and telomeric to NR2F2-AS1 is the NR2F2 gene, which is transcribed from centromere to telomere and in which alternate splicing results in multiple transcript variants (https://www.ncbi.nlm.nih.gov/gene/7026). NR2F2 codes for a member of the steroid thyroid hormone superfamily of nuclear receptors, a ligand-inducible transcription factor involved in the regulation of many different genes (31,32). A possible consequence of the t(X;15)(q22;q26) might also be deregulation of NR2F2 in a manner similar to that which occurs with the fusion of the collagen type I alpha 1 chain gene (COL1A1) with the plateletderived growth factor subunit B gene (PDFGB) , the ubiquitin specific peptidase 6 gene (USP6), and FYN proto-oncogene, Src family tyrosine kinase gene (FYN) in dermatofibrosarcoma protuberans, aneurysmal bone cyst, and epithelioid osteoblastoma, respectively (33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Next and telomeric to NR2F2-AS1 is the NR2F2 gene, which is transcribed from centromere to telomere and in which alternate splicing results in multiple transcript variants (https://www.ncbi.nlm.nih.gov/gene/7026). NR2F2 codes for a member of the steroid thyroid hormone superfamily of nuclear receptors, a ligand-inducible transcription factor involved in the regulation of many different genes (31,32). A possible consequence of the t(X;15)(q22;q26) might also be deregulation of NR2F2 in a manner similar to that which occurs with the fusion of the collagen type I alpha 1 chain gene (COL1A1) with the plateletderived growth factor subunit B gene (PDFGB) , the ubiquitin specific peptidase 6 gene (USP6), and FYN proto-oncogene, Src family tyrosine kinase gene (FYN) in dermatofibrosarcoma protuberans, aneurysmal bone cyst, and epithelioid osteoblastoma, respectively (33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Giving the important role of COUP-TFII on glucose and lipid metabolism (Ashraf et al, 2019), we hypothesized that COUP-TFII might regulate myofibroblast differentiation through metabolism reprogramming. Our proteomic data revealed that COUP-TFII promotes the expression of proteins enriched in metabolic process critical for myofibroblasts, in particular, suppression of FAO and enhancement of glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Chicken ovalbumin upstream promoter-transcription Factor II (COUP-TFII, also known as NR2F2) is an orphan member of the nuclear receptor family with unknown endogenous ligands (Pereira, Qiu et al, 1999). Since COUP-TFII has been reported to regulate metabolic functions (Ashraf, Sanchez et al, 2019, Li, Xie et al, 2009, Planchais, Boutant et al, 2015, we evaluated whether it played an important role in fibrosis. Downstream proteins under COUP-TFII control tend to be involved in energy production, anabolic pathways, and cell cycle progression, all of which impact on cell proliferation , Planchais et al, 2015, Wu, Kao et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 18, 2021. ; https://doi.org/10.1101/2021.06.18.448955 doi: bioRxiv preprint but can involve more complex interactions such as heterodimerization with COUP-TFs and RXR. Specifically, HNF4α co-interaction with COUP-TFII elicits tissue-specific inhibitory and synergistic gene expression effects (Ashraf et al, 2019). Alternatively, COUP-TFII dimerizes with RXR and competes with HNF4α/RXR for the same binding site or sequesters RXR thereby limiting HNF4α/RXR signaling events (Ashraf et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, HNF4α co-interaction with COUP-TFII elicits tissue-specific inhibitory and synergistic gene expression effects (Ashraf et al, 2019). Alternatively, COUP-TFII dimerizes with RXR and competes with HNF4α/RXR for the same binding site or sequesters RXR thereby limiting HNF4α/RXR signaling events (Ashraf et al, 2019).…”
Section: Introductionmentioning
confidence: 99%